Estudio de retencion de metales pesados en agua sintéticas (Preparadas en el Laboratorio) Utilizando como lecho Filtrante la Fibra de Cabuya Furcraea Andina como Alternativa de Bioremendiación. - Baldeon Cajo, José Enrique (2013)
This paper presents information of research on sisal fiber (Furcracea Andina), on the other hand the work gathers both bibliography and, experimental laboratory work, acts that make of this, an investigative work that which allows, generating knowledge to academic level and growth to level professional.